NLR and Intestinal Dysbiosis-Associated Inflammatory Illness: Drivers or Dampers? - Elias-Oliveira, Jefferson; Leite, Jefferson Antônio; Pereira, Ítalo Sousa; Guimarães, Jhefferson Barbosa; Manso, Gabriel Martins da Costa; Silva, João Santana; Tostes, Rita Cássia; Carlos, Daniela (Frontiers in Immunology, 2020)
The intestinal microbiome maintains a close relationship with the host immunity. This connection fosters a health state by direct and indirect mechanisms. Direct influences occur mainly through the production of short-chain fatty acids (SCFAs), gastrointestinal hormones and precursors of bioactive molecules. Indirect mechanisms comprise the crosstalk between bacterial antigens and the host’s innate immune system. Conversely, intestinal dysbiosis is a condition found in a large number of chronic intestinal inflammatory diseases, such as ulcerative colitis and Crohn’s disease, as well as in diseases associated with low-grade inflammation, such as obesity, type 1 and 2 diabetes mellitus and cardiovascular diseases. NOD-Like receptors (NLRs) are cytoplasmic receptors expressed by adaptive and innate immune cells that form a multiprotein complex, termed the inflammasome, responsible for the release of mature interleukin (IL)-1β and IL-18. NLRs are also involved in the recognition of bacterial components and production of antimicrobial molecules that shape the gut microbiota and maintain the intestinal homeostasis. Recent novel findings show that NLRs may act as positive or negative regulators of inflammation by modulating NF-κB activation. This mini-review presents current and updated evidence on the interplay between NLRs and gut microbiota and their dual role, contributing to progression or conferring protection, in metabolic and inflammatory diseases.